The Oocyte’s Nucleolus Precursor Body: The Globe for Life - Benc, Michal; Pendovski, Lazo; Murin, Matej; Strejcek, Frantisek; Morovic, Martin; Prochazka, Radek; Laurincik, Jozef (Walter de Gruyter GmbH, 2018)
Abstract The nucleolus is the cell organelle responsible for ribosome synthesis and, hence, for protein synthesis. In the mammalian oocyte, the nucleolus compacts into a dense sphere with no ribosome synthesis well in advance of ovulation. It seems, that this body is of utmost importance for the development of the embryo. It is unknown, however, how it exerts this essential function. During the last two decades, great attention has been paid to the study of nucleogenesis in oocytes and early embryos, with transcription of ribosomal DNA being evaluated as one of the criteria of normal development. In this review, we summarize some aspects of nucleolus transformation during oocyte growth, as well as during early embryonic development with possible impact on the quality of the embryos used in biomedical research. This knowledge in connection with further observations will substantially contribute to the development of new criteria suitable for evaluation of oocytes and embryos used in biomedical application.